A Dose-Response Investigation of a Micronized Porous Ceramic Particle to Improve the Health and Performance of Post-weaned Pigs Infected With Salmonella enterica Serotype Typhimurium - Davis, Emily M.; Wallace, Kayla P.; Cruz Penn, Michael J.; Petry, Amy L.; Broadway, Rand; Burdick Sanchez, Nicole C.; Carroll, Jeffery A.; Ballou, Michael A. (Frontiers in Animal Science, 2022)
The objective was to investigate the effects of supplementing increasing concentrations of PowerGuard (PG), a micronized ceramic particle, to weaned pigs on health and performance following a Salmonella enterica serotype Typhimurium infection. Forty barrows were transported to the USDA facility in Liberty, TX. Pigs were randomly assigned to one of five treatments (n=8): (1) Uninfected Control (CON), no Salmonella typhimurium (ST) and no PG treatment; (2) Infected Control (ST), infected with ST but no PG treatment; (3) PG0.05, infected with ST and supplemented with 0.05% PG; (4) PG0.25, infected with ST and supplemented with 0.25% PG; (5) PG0.50, infected with ST and supplemented with 0.50% PG. All pigs were enrolled at 21.5 ± 1.33 d of age, and did not differ in initial BW (1.98 ± 0.09 kg). Pigs were anesthetized to insert temperature recording devices into the abdominal cavity. Pigs were offered feed and water ad libitum. Pigs in ST, PG0.05, PG0.25, and PG0.50 were infected orally with 1.75 x 107 colony forming units of Salmonella typhimurium on d 7. Pig body weights and peripheral blood samples were collected on d 0, 7, 10, 14, and 21. Pigs were harvested on d 21 and ileum and liver samples collected for histopathological analyses. There was no treatment difference for final BW(P ≥ 0.201). There was a tendency (P = 0.087) for a treatment difference in fecal score; ST and PG0.50 had more loose fecal scores than CON and PG0.25. There was a treatment × time interaction for intraperitoneal temperature(P < 0.0001); PG0.05, PG0.25, and PG0.50 had attenuated febrile responses during the acute post-infection period compared with ST. There was a treatment × time interaction for total leukocyte counts (P = 0.007); PG treatments reduced leukocytosis post-infection compared with ST. Supplementing PG0.25 improved many health and performance variables when pigs were infected with Salmonella typhimurium. Further, supplementing PG0.05 attenuated the febrile response and many hematological variables. However, supplementing PG0.5 did not improve many aspects of health or performance. Therefore, supplementing PowerGuard between 0.05% and 0.25% of the diet may play a role in protecting weaned pigs from disease caused by Salmonella.